Comparison of the static frictional resistance and surface topography of ceramic orthodontic brackets: an in vitro study - AlSubaie Mai; Talic Nabeel (Sciendo, 2017)
The aim of this study was to investigate the frictional resistance (FR) and surface topography of newly available polycrystalline alumina (PCA) ceramic brackets characterised by a yttria-stabilised zirconia (YSZ) coating of the slots, compared with monocrystalline alumina (MCA) ceramic brackets and stainless steel (SS) brackets.